Ekspor Karet Indonesia ke-15 Negara Tujuan Utama Setelah Pemberlakuan Kebijakan ACFTA - Lembang, Marlina Banne; Pratomo, Yulius (Jurnal Trikonomika, 2013)
The objective of this study is to examine factors affecting Indonesiaâs rubber export performance to Indonesiaâs 15 main trading partners after the implementation of ACFTA. This research employs Bergstrand Gravity Model (1985) using 105 observation for 15 countries from 2004 to 2010. Then, the gravity model is estimated by applying random effects (RE) model. The results show that, first, GDP per capita of Indonesiaâs main trading partners have significantly positive impact on export. Surprisingly, distance has significantly positive effect on Indonesiaâs rubber export. Further, Indonesiaâs rubber major export destinations are the member of ACFTA, i.e. China and Singapore. Last, some of the non member countries are still potential to be Indonesiaâs rubber market. Therefore, the Government of Indonesia should increase trading with them.